Foliar magnesium fertiliser remediates induced Mg deficiency in cation-rich vineyard soils - Cody Copp (OENO One)
Magnesium (Mg) is an essential plant macronutrient that influences various physiological processes, including photosynthesis and carbohydrate translocation. Magnesium deficiency in grapevines (Vitis vinifera L.) can impair vine performance, productivity, and fruit quality. High soil concentrations of the cationic nutrients potassium and calcium can reduce the uptake of Mg, which can induce Mg deficiency in grapevines, even with high soil Mg. This study compares the effectiveness of foliar-applied magnesium sulfate (MS) and chelated magnesium (MC) fertilisers for mitigating induced Mg deficiency symptoms associated with a cation-rich soil in the Columbia Basin growing region. An experiment was conducted in a commercial Mourvèdre vineyard block near Milton-Freewater, OR, USA, from 2023 to 2024, in which fertilisers were applied at three-week intervals between bloom and harvest. The severity of visible Mg deficiency symptoms was assessed, leaf nutrients were quantified, and fruit quality at harvest was analysed. MS significantly increased leaf Mg and decreased the severity of Mg deficiency symptoms compared to the control and MC. Fruit yield components and chemistry were not significantly altered by the fertiliser treatments. It is likely that the MS treatment was more effective at improving Mg deficiency due to the higher Mg dose compared to the MC fertiliser, which appeared similarly effective relative to the dose. The effect of MS was more pronounced when leaf Mg was below the regionally recommended whole leaf Mg threshold of 0.25 %, and the effect largely disappeared when leaf Mg increased above this threshold. These results justify the use of foliar applied magnesium sulfate fertiliser as a lower cost solution to correct induced Mg deficiency in cation-rich soils with poor Mg uptake. Moreover, this study verifies the recommended leaf Mg threshold and demonstrates the importance of leaf nutrient analysis over visual diagnosis for accurate diagnosis and correction of Mg deficiencies in grapevine.